Molecular and dissociative adsorption of oxygen on au-pd bimetallic clusters: role of composition and spin state of the cluster - Dar, Manzoor Ahmad; Krishnamurty, Sailaja (Acs Omega, 2019)
Utilization of molecular oxygen as an oxidizing agent in industrially important reactions is the ultimate goal to design environmentally benign processes under ambient conditions. However, the high thermal stability and a large O-O dissociation barrier in O-2 molecule pose a great challenge toward its successful application in the oxidative chemistry. To achieve this goal, different catalysts based on monometallic and bimetallic clusters have been developed over the years to promote binding and dissociation of molecular oxygen. The successful design of efficient metal cluster catalysis needs an in-depth knowledge of synergistic effects between different metal atoms and intrinsic catalytic mechanisms for O-2 adsorption and dissociation. Here, we present a systematic theoretical investigation of reaction pathways for O-2 adsorption and dissociation on Au-8, Pd-8, and Au8-nPdn (n = 1-7) nanoclusters in different spin states. The density functional calculations point out that the O-2 dissociation barriers can be significantly reduced with the help of certain bimetallic clusters along specific spin channels. Our results particularly indicate that Au5Pd3 and Au1Pd7 show very large O-2 binding energies of 1.76 and 1.69 eV, respectively. The enhanced O-2 binding subsequently leads to low activation barriers of 0.98 and 1.19 eV along the doublet and quartet spin channels, respectively, without the involvement of any spin flip-over for O-2 dissociation. Furthermore, the computed O-2 dissociation barriers are significantly low as compared to the already reported barriers (1.95-3.65 eV) on monometallic and bimetallic Au-Ag clusters. The results provide key mechanistic insights into the interaction and dissociation of molecular oxygen with Au-Pd clusters, which can prove informative for the design of efficient catalysts for oxidative chemistry involving molecular oxygen as a reactant.